Low Prevalence of Hepatitis C Virus Genotype -1b in Chronic Liver Disease Patients in India - Thakur, V (EJIFCC, 2003)
BACKGROUND: The Hepatitis C Virus (HCV) genome shows significant heterogeneity due to a high rate of mutatio; this has a potential bearing on the outcome of interferon therapy. Genotype-1b is known to be less responsive to interferon. We studied the spectrum of HCV genotypes in chronic liver disease (CLD) patients in India. MATERIAL AND METHODS: HCV RNA was extracted from the serum of 44 randomly selected cases of HCV-related CLD, proven by liver biopsy, (mean age of patients 40±15 yr., cirrhotic: 32%) and RT PCR was carried out. The amplicon of 240 bp (second nested PCR) was hybridized to the probes (type specific) coated on to a nitrocellulose membrane. Following this, streptavidin, labeled with alkaline phosphatase, was added to bind with biotinylated hybrid, which with chromogen type-specific band formation resulted. Patients were classified on the occurrence of one (Group I), two (Group II) or multiple genotypes (Group III). RESULTS: Genotypes 1 and 3 were the commonest genotypes, followed by type 2 and the rare genotype 4b in a lone patient. Genotype 1 was seen in 39% (1a 23%, and 1b 16%) while genotype 3 in 45% (3a 23% and 3b 7%) patients. Eighty percent (35 of 44) patients had the single genotype (Group I, mean age 46 ± 8 yr.), 14% had two genotypes (Group II, mean age 36 ± 16 yr.) and the remaining (Group III, mean age 22 ± 9 yr.) had multiple genotypes. Serum ALT levels in these three groups of patients were 117 ± 92, 85 ± 45 and 49 ± 7 IU/L respectively. CONCLUSIONS: 1. Genotypes 1 and 3 are common in India, with subtype 1b not so common, 2. A unique genotype 4 b was detected in one patient, 3. Indian patients have the possibility of good antiviral response to interferon therapy in chronic HCV infection.